2007
DOI: 10.1139/x07-046
|View full text |Cite
|
Sign up to set email alerts
|

Use of different seed tissues for separate biparentage identification of dispersed seeds in conifers: confirmations and practices for gene flow in Pinus densiflora

Abstract: To investigate how accurately biparentage assignments for coniferous seeds can be improved by using different kinds of seed tissues, we assigned biparentage to dispersed seeds in a natural stand of Pinus densiflora Siebold & Zucc. (288 mature trees) using two procedures: with or without megagametophyte haplotype data (“MH” and “ordinary” procedures, respectively). Using archived clones, we confirmed the conifer-specific modes of inheritance of three kinds of seed tissues from certain maternal trees using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The estimated genetic diversity of the trees, seeds, maternal alleles, and paternal alleles in 8 fragmented populations was similar to those in a natural P. densiflora population surrounded by many mature trees (Iwaizumi et al 2007) or a preserved P. densiflora population almost isolated from other mature trees (Lian et al 2001). Using microsatellite loci, H E value was estimated to be 0.898 (Iwaizumi et al 2007) and 0.915 (Lian et al 2001) in trees, ranged from 0.862 to 0.934 (Lian et al 2001) in seeds, and ranged from 0.785 to 0.937 (Iwaizumi et al 2010) in gametic alleles of the seeds.…”
Section: Genetic Diversity In P Densiflora Populationssupporting
confidence: 53%
See 2 more Smart Citations
“…The estimated genetic diversity of the trees, seeds, maternal alleles, and paternal alleles in 8 fragmented populations was similar to those in a natural P. densiflora population surrounded by many mature trees (Iwaizumi et al 2007) or a preserved P. densiflora population almost isolated from other mature trees (Lian et al 2001). Using microsatellite loci, H E value was estimated to be 0.898 (Iwaizumi et al 2007) and 0.915 (Lian et al 2001) in trees, ranged from 0.862 to 0.934 (Lian et al 2001) in seeds, and ranged from 0.785 to 0.937 (Iwaizumi et al 2010) in gametic alleles of the seeds.…”
Section: Genetic Diversity In P Densiflora Populationssupporting
confidence: 53%
“…Polymerase chain reaction (PCR) amplification was performed using the DNA Engine™ Model PTC-200 (MJ Research Inc., Hercules, CA) and a Multiplex PCR kit (Qiagen Inc., Valencia, CA). The PCR reaction was modified based on the standard SSR thermal reaction conditions recommended by the manufacturer (Iwaizumi et al 2007). The amplified fragment sizes were determined with an ABI PRISM 3100 genetic analyzer (Applied Biosystems Inc., Foster City, CA) against a GENESCAN-500 LIZ Size Standard (Applied Biosystems).…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we assume that 'seed coat formation' equates with seed formation, our results indicate that seed formation occurs regardless of post-fertilization effects such as pollen quality. In addition, as DNA markers (SSRs) have confirmed that a seed coat is entirely maternally inherited diploid seed tissue in P. densiflora (Iwaizumi et al 2007), it is quite reasonable to assume that seed formation itself is not influenced by the paternally derived genetic effects via pollen gametes. Thus, pollination itself could be regarded as a 'trigger,' and hence the prerequisite condition, for seed formation.…”
Section: Seed Formationmentioning
confidence: 99%
“…It has also been important to conserve the natural genetic resources and the within-population genetic diversity against potential depletion or contamination through overcutting or plantation practices. Highly polymorphic microsatellite (simple sequence repeat; SSR) markers have enhanced molecular studies of Japanese conifer species, in particular, genotypic discrimination of clones (e.g., HIRAO et al, 2006), gene flow in seed orchards and natural populations (e.g., MORIGUCHI et al, 2005;GOTO et al, 2005;IWAIZUMI et al, 2007;LIAN et al, 2008), and inter-population genetic structure (e.g., TAKAHASHI et al, 2005).…”
Section: Introductionmentioning
confidence: 99%